Dominant Association Species in Binary Mixtures of Methanol, Ethanol and Propanol in Nonpolar Solvents (Journal of Sciences, Islamic Republic of Iran)
The molecular associations in the binary mixtures of (methanol/solvent), (ethanol/solvent) and (propanol/solvent) were studied using NMR, FTIR and VLE data at different temperatures. The activity coefficients as the most important quantities representing the mixture deviation form ideal behavior were evaluated by using various association models to express the physical and chemical contributions of the activity coefficients. The parameters of these models were calculated. The results indicated that for methanol and ethanol the dominant associated species are the tetramer whereas for propanol it is the trimer. The differences between the parameters of activity coefficient models were calculated by considering the physical and chemical contributions separately and were expressed in terms of residual parameters for the activity coefficient models. The parameters of van Laar model were corrected on the basis of the existing dominant species in the associated mixtures and a simple linear relation was obtained for the parameters of the model for the dominant species in terms of the parameters for monomer